Entre planárias, tardígrados e drosófilas: as contribuições de Rosina de Barros (1909-1994) para a institucionalização da genética no Brasil - Malinosky, Évelin Moraes da Silva (2021)
This study addresses the institutionalization process of genetics in Brazil, more specifically at the Faculty of Philosophy, Sciences and Letters of the University of São Paulo, focusing on the academic trajectory of Professor Rosina de Barros. To that end, we analyzed her articles and searched for her professional documents kept in the General Archive of the University of São Paulo, besides consulting the Faculty’s Yearbooks. With this study, we aim to reflect on the relationship between gender and science, presenting the participation of Rosina de Barros in the development of Brazilian genetics